ANALISIS PENGARUH PRODUK, HARGA, PROMOSI DAN LOKASI TERHADAP MINAT BERKUNJUNG WISATAWAN KE TAMAN SATWA TARU JURUG SURAKARTA - Andriyani, Fanata; Triyanto, Triyanto (Riset Manajemen dan Akuntansi, 2019)
The more developed tourism development has made the tourism sectors compete to improve the marketing of tourism products and make improvements or development in all fields that follow the current era in order to attract tourists. This can be achieved because of the marketing management that is useful to help achieve the desired target by the tourism sector. The definition of tourism is a phenomenon of the movement of people, goods, and services, which is very complex. It is closely related to organizations, institutional and individual relations, service needs, service provision needs, and so on. At this time the products, facilities, facilities and, infrastructure offered by Jurug Park are still relatively not satisfying tourist satisfaction. With the development and ongoing developments currently expected to attract more attention and curiosity of tourists to visit. Based on the results of the analysis and discussion carried out in the previous chapter, some conclusions can be drawn that the product variable has a positive and significant effect on the interest of visiting tourists The price variable has a negative and not significant effect on the interest of visiting tourists; The promotion variable has a negative and not significant effect on tourist interest, location variable has a positive and significant effect on tourist interest in visiting Taru Jurug Wildlife Park.